The Potential of Rhizophoramucronata in Extracting the Chemical Composition and Biological Activities as Mangrove Plants: A Review - Nour, A. H.; Nitthiyah, Jeyaratnam; Manal, S. Omer (AENSI Publishing, 2016)
In this review article, the general importance of mangrove plants including the direct and indirect uses was presented. Attemptswere made to create awareness as well as emphasize the potentiality of mangrove plants especially for th benefits. Specific emphasis was laid on the Rhizophora species.An updated report on the conventional extraction methods of the chemical constituents from this plant species is presented herein.Also, biological activities of the minor and m extracted from Rhizophora plants are discussed. Furthermore, an updated report was made on the chemical groups present in Rhizophora plants with direct emphasis on the four commonly investigated species which are R. apiculata, R. mangle, R. mucronata,and R. stylosa. Structures of some extracted compounds obtained from Rhizophora plants are also illustrated. In effect, Rhizophora species have been presented here as a viable alternative source of many biological and chemically active compounds which are already known to be of great economic and pharmaceutical importance.Moreover, efforts were made to expose the potential of Rhizophora plants as possible sources of many yet unknown chemical compounds which could provide great beneficial activities.